2010
DOI: 10.5194/npg-17-569-2010
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of the seismograms for tsunami warning

Abstract: Abstract. The complexity in the tsunami phenomenon makes the available warning systems not much effective in the practical situations. The problem arises due to the time lapsed in the data transfer, processing and modeling. The modeling and simulation needs the input fault geometry and mechanism of the earthquake. The estimation of these parameters and other aprior information increases the utilized time for making any warning. Here, the wavelet analysis is used to identify the tsunamigenesis of an earthquake.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The authors also calculated the wavelet packet variance and the wavelet correlation coefficients. Chamoli et al (2010) analysed the tsunami-generating and non-tsunamigenerating earthquakes recorded at different stations to identify the tsunami-genesis of an earthquake. The authors examined the frequency of the seismogram components in the time domain using wavelet transform.…”
Section: Datamentioning
confidence: 99%
“…The authors also calculated the wavelet packet variance and the wavelet correlation coefficients. Chamoli et al (2010) analysed the tsunami-generating and non-tsunamigenerating earthquakes recorded at different stations to identify the tsunami-genesis of an earthquake. The authors examined the frequency of the seismogram components in the time domain using wavelet transform.…”
Section: Datamentioning
confidence: 99%
“…Wavelet methods have shown significant contributions in different fields: gravity and magnetic source characterization and source edge detection [3,[16][17][18], climatic signals [19], tsunami warning [20,21], and different time series analyses [22,23]. Shannon entropy is a measure of information of any distribution and has been found to be helpful for tsunami warnings [24,25], climatology and hydrology [26,27], and earthquake analysis [28,29] in past case studies.…”
Section: Introductionmentioning
confidence: 99%
“…The energy distribution is shifted at the boundary by half of the step-width using Walsh low pass sequenecy filtering method. Recently, several researchers have suggested that wavelet based algorithm could be an appropriate choice to handle the nonstationary part of the geophysical signal (Morlet et al 1982;Mallat 1989;Wickerhauser 1994;Kumar and Foufoula-Georgiou 1997;Oppenheim et al 1999;Boggess and Narcowich 2001;Frantziskonis and Denis 2003;Soliman et al 2003;Misti et al 2007;Chamoli et al 2007;Pan et al 2008;Chamoli et al 2010;Adamowski and Chan 2011;Chandrashekhar and Rao 2012;Perez-Munoz et al 2013). Researchers have invariably used wavelet transform to solve geophysical characterization problem.…”
Section: Introductionmentioning
confidence: 99%